2017
DOI: 10.1590/1982-0224-20170056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of diet composition and its relation to morphological characteristics in juvenile fish of three lutjanid species in a Mexican Pacific coastal lagoon

Abstract: The main goal of this research was to investigate the differences in diet composition among three species of the genus Lutjanus inhabiting a coastal lagoon as juveniles. The working hypothesis was that these species feed on a common base of food resources and therefore, some niche overlap is present in terms of general diet composition. However, changes in the trophic niche with size and differences in some morphological traits among species explain observed differences in diet. Fish were collected during 42 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This statement is supported by the results from the research which stated that Chlorophyta and Cyanophyta discovered in the guts of plecos fish in the Langat River, are relatively abundant in the habitat (Samat et al 2016). Fishes generally adjust the food types to the size of their mouth openings, while the larger ones tend to consume more food (Zuluaga-Gomez et al 2016;Aguilar-Betancourt et al 2017;Winkler et al 2017). The IP analysis obtained, showed that P. pardalis is included in the opportunist fish group because it is able to utilize the food available in the river.…”
Section: Pterygoplichthys Pardalis Index Preponderance In Ciliwung Rivermentioning
confidence: 92%
See 2 more Smart Citations
“…This statement is supported by the results from the research which stated that Chlorophyta and Cyanophyta discovered in the guts of plecos fish in the Langat River, are relatively abundant in the habitat (Samat et al 2016). Fishes generally adjust the food types to the size of their mouth openings, while the larger ones tend to consume more food (Zuluaga-Gomez et al 2016;Aguilar-Betancourt et al 2017;Winkler et al 2017). The IP analysis obtained, showed that P. pardalis is included in the opportunist fish group because it is able to utilize the food available in the river.…”
Section: Pterygoplichthys Pardalis Index Preponderance In Ciliwung Rivermentioning
confidence: 92%
“…The joint use of available diet resources by the fish size groups tends to cause overlapping niches. Overlapping occurs when the food resources are shared by two or more types of fish (Sentosa and Satria 2015;Aguilar-Betancourt et al 2017;Westerborn et al 2018). The results from the analysis of overlapping niches showed that the relationship between the large and medium fish groups has a greater value (0.77) compared to that of other groups (Table 4).…”
Section: Feeding Niches Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The Lutjanus sp. genus is a marine species of snapper native to the Atlantic coastal waters of the Americas from Massachusetts to southern Brazil with potential for captive culture, with great productive performance, demand for the consumer market and high market value (Freitas, et al, 2011;Aguilar-Betancourt, et al, 2017). Thus, the development of the marine aquaculture productive chain, highlighting the mutton snapper Lutjanus analis culture, reduces extractive fishing and preserves the natural stocks, and provides a tool for protecting this significant group of reef fish (Sanches, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Within these species, the Colorado snapper (L. colorado) reaches sizes up to 90 cm in total length and has a wide distribution in the tropical and Northeastern Pacific (TEP) from the coasts of California (USA) to Panama, including the GC. This species inhabits coastal reefs down to 70 m in depth, but juveniles are associated with coastal waters and estuaries (Allen, 1985(Allen, , 1995; this species has been captured in artisanal fisheries (Aguilar-Betancourt et al, 2017;Allen, 1995) and is also considered as a potential aquaculture species (Hernandez et al, 2018).…”
mentioning
confidence: 99%